Pembuatan dan Analisa Performa Tekanan dan RPM Pada Komponen Swing Hidrolik Di Alat Peraga Mini Excavator - Aji, Angga Prasetio; Prayoga, Benidiktus Tulung; Winarto, Felixtianus Eko Wismo; Prihadianto, Braam Delfian; Bahari, Galuh (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The Vocational School Education is a university-level higher education program that places greater emphasis on practical fieldwork relevant to industry needs rather than academic theoretical knowledge. In Indonesia, vocational school programs or diplomas play a crucial role in the development and scientific research. The creation of a mini excavator model is a research and innovation project aimed at supporting students' practical training activities. The development of hydraulic swing components is used to enhance the components of the mini excavator model, which will later be expanded for educational purposes in the hydraulic drive system. The ultimate goal of this research is to manufacture hydraulic swing components that will be installed in the mini excavator model, with the final objective being to determine the pressure and rpm performance of these hydraulic swing components. Based on the conducted research, operating the mini excavator model requires a radius dimension or distance from the center point to the warning line of 3 m², and the maximum pressure for the mini excavator model is 150 kgf/cm², resulting in 11.17 rpm. Meanwhile, the allowable pressure for operating the hydraulic swing components in the mini excavator model is 100 kgf/cm², resulting in 8.54.